Recovery Efforts for Victims of Terrorism Crimes in Indonesia - Mula Sihombing; Yasmirah Mandasari Saragih; Mhd. Azhali Siregar; Welli Nirpa Pasaribu; Delianto Habeahan (International Journal of Law, Crime and Justice, 2024)
Terrorism is a criminal act that poses a serious threat to the sovereignty of every country which can pose a danger to security, world peace and disrupt the welfare of society. A crime that has an extraordinary traumatic impact on the victim so that it requires efforts to recover from the crime of terrorism. In this case, the role of the state is really needed in order to provide the rights of the victims of this crime. The purpose of this research is to find out what efforts are being made to help the recovery of victims of criminal acts of terrorism in Indonesia and to find out what obstacles are faced when making efforts to recover victims of criminal acts of terrorism in Indonesia. The research method used is a normative legal research method which uses library materials as main data, namely secondary legal materials. Then the legal materials are analyzed descriptively qualitatively to obtain results and conclusions from the problem formulations that have been determined. The results of this research indicate that efforts to recover or medically treat victims of terrorism continue to use the same legal basis as the disaster law which has the authority to provide assistance to victims in hospitals. Because all victims of criminal acts of terrorism are the responsibility of the government, which in practice always faces many obstacles.